An iron-based bone implant with acidified passivation film to accelerate dissolution and a preparation method thereof
By adding potassium chloride and copper to the iron-based bone implant material, the reaction of potassium chloride and copper is used to generate a porous structure and an internal acidic environment, the problem of slow degradation caused by passivation film is solved, and the iron-based material is realized rapid degradation and bone tissue repair.
Patent Information
- Application Number
- CN202210354112.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-06
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2042-04-06
AI Technical Summary
Due to the existence of passivation membrane, existing iron-based bone implant materials have a slow degradation rate and are difficult to meet the needs of bone tissue repair.
Iron-potassium chloride-copper material is used to react with potassium chloride and copper dissolved in body fluids to produce a porous structure and an internal acidic environment, which promotes the dissolution of the passivation film, thereby accelerating the degradation of iron-based materials.
It significantly improves the degradation rate of iron-based materials, enhances the mechanical properties and biocompatibility of bone implants, reduces the shielding effect of passivation film on the reaction medium, and promotes the repair of bone tissue.
Abstract
Description
Technical Field
[0001] The invention relates to a biomedical iron-based bone implant, belonging to the field of degradable biomedical metals. Background Art
[0002] Promoting regeneration of bone defects caused by trauma, infection, tumors or inherent genetic diseases through bone graft materials is a huge clinical challenge. Autologous bone transplantation is still considered the "gold standard" in clinical practice and the most effective method for bone regeneration. However, limited bone supply and donor site complications are the main disadvantages of autologous bone transplantation. It is imperative to develop synthetic bone implants to overcome these limitations and improve the effects of bone repair and regeneration.
[0003] There are basically two types of artificial bone implants: one is non-biodegradable implants made of inert materials such as stainless steel, titanium and its alloys, and cobalt-chromium (Co-Cr) alloys. They have good biocompatibility, high wear resistance, and excellent mechanical properties, but they take a long time to heal and still need to be removed from the human body after healing is completed, because their long-term use leads to complications such as allergic reactions, necrosis, inflammation, pain, and even cancer. In addition, surgical removal of non-biodegradable implants made of these inert materials is not only very painful, but also brings additional financial burdens to patients.
[0004] The other is biodegradable bone implants made of polymers, ceramics, and metals. They temporarily support the healing process of diseased tissues or organs, and then gradually degrade in the human body and are slowly replaced by growing tissues. The degradation products are non-allergenic and non-carcinogenic compounds that can be excreted from the body through the natural physiological process of the human body. Polymers and ceramics have good biocompatibility, but the shortcomings of insufficient mechanical properties seriously limit their practical application. At the same time, metal-based materials have received more and more attention due to their excellent comprehensive mechanical properties. Among them, magnesium-based materials, zinc-based materials, and iron-based materials are very promising as biodegradable bone implants. However, magnesium-based materials degrade very quickly (within 1-4 months) during physiological processes and are accompanied by the production of a large amount of hydrogen. Too fast degradation will cause the implant to lose its mechanical integrity prematurely. In contrast, zinc-based materials are characterized by an ideal degradation rate and can stimulate the formation of remodeled bone tissue, but the mechanical strength of zinc-based materials is low and is not enough to meet the needs of load-bearing bones. In recent years, iron-based materials have attracted much attention due to their good mechanical properties and the fact that they do not produce hydrogen during degradation. At the same time, iron is one of the important trace elements in the human body and is involved in a variety of metabolic processes, such as oxygen transport, DNA synthesis, and electron transfer. In vivo studies have demonstrated the suitability of iron-based materials as degradable bone implants. However, the passivation film composed of dense corrosion products such as iron hydroxide, iron carbonate and iron phosphate layers greatly hinders the degradation reaction. Therefore, it is necessary to propose a method to reduce the passivation film and accelerate the degradation rate of iron-based implant materials. Summary of the invention
[0005] In view of the problem that the passivation film in the prior art causes the iron-based implant material to degrade slowly and is difficult to meet the requirements of bone tissue repair, the present invention proposes to prepare an iron-potassium chloride-copper implant material. During the degradation process of the implant material, potassium chloride has a large solubility in body fluids and first releases chloride ions and potassium ions, producing a porous structure in the iron matrix, increasing the reaction area of copper and thus promoting the dissolution of copper; there is a potential difference between the standard potential of copper (+0.34V) and the standard potential of the iron matrix (-0.44V), which promotes electron migration under the action of the potential difference, thereby accelerating the dissolution of copper, and the cuprous ions (Cu 2+) produced by the dissolution of copper + ) Part of it will react with free chloride ions to form cuprous chloride (CuCl), and the other part will exist in the body fluid as free cuprous ions. Cuprous chloride and cuprous ions will undergo hydrolysis reaction under the passivation film and in the pit (2CuCl+H2O→Cu2O+2H + +2Cl - ,2Cu + +H2O→Cu2O+2H +), and creates an internal acidic environment. The internal acidic environment will greatly increase the solubility of the iron passivation film and ultimately promote the dissolution of the passivation film from the inside. At the same time, the internal acidic environment will acidify the active sites, promote the stabilization of metastable pitting nuclei and the expansion of mature pits, and promote intergranular corrosion at the bottom of the pits. Therefore, the passivation effect of the passivation film is gradually reduced in the internal hydrolytic acidic environment, and new reaction media are allowed to enter, thereby increasing the dissolution rate of iron-based materials. The copper ions released by copper dissolution play an important role in driving cell respiration, resisting oxidative stress and other physiological processes as cofactors of several enzymes. At the same time, copper ions can act on bacterial proteins, thereby inducing the breakage of protein ionic bonds and causing protein inactivation. In addition, copper ions can also bind to bacterial DNA, thereby inhibiting its replication.
[0006] In order to achieve the purpose of reducing the passivation film and increasing the degradation rate of the iron-based implant material, the present invention provides the following technical solutions:
[0007] The invention discloses an iron-based bone implant with an acidified passivation film that accelerates the dissolution. The iron-based bone implant is composed of an iron-potassium chloride (3.7 wt.%) matrix and copper, wherein the mass percentage of the copper is 0.3-1.5 wt.%.
[0008] Furthermore, in the iron-based bone implant with an acidified passivation film that accelerates dissolution, the mass percentage of copper is 0.5-1.2wt.%.
[0009] Furthermore, in the iron-based bone implant with an acidified passivation film that accelerates dissolution, the mass percentage of copper is 0.9wt.%.
[0010] Furthermore, the copper powder has a size of 30-60 microns, the iron powder has a size of 50-70 microns, and the potassium chloride powder has a size of 10-45 microns.
[0011] In the iron-based bone implant in which the acidified passivation film accelerates dissolution, potassium chloride can be quickly dissolved around, leaving numerous evenly distributed microscopic pores. In addition, the potential difference between the copper and iron matrix accelerates electron migration, thereby promoting the release of cuprous ions, a portion of which forms cuprous chloride with chloride ions, and a portion exists as free cuprous ions. The hydrolysis of cuprous chloride and cuprous ions inside the passivation film causes the trapped solution to become acidified, promoting the generation and development of corrosion pits on the inner iron-based surface. As degradation proceeds, the passivation film becomes loose and porous, making it difficult to inhibit the reaction medium from reacting with the internal iron matrix, ultimately accelerating the entire degradation process.
[0012] Furthermore, the porosity of the iron-based bone implant in which the acidified passivation film accelerates dissolution is 17-29%.
[0013] Furthermore, the porosity of the iron-based bone implant in which the acidified passivation film accelerates dissolution is 23-27%.
[0014] The iron-based bone implant with acidified passivation film that accelerates dissolution is prepared by the following technical steps:
[0015] Step 1 Mechanical Mixing:
[0016] After the copper powder is dried at a constant temperature, a certain mass is weighed and added to the iron-potassium chloride (3.7 wt.%) mixed powder in equal amounts in 3-5 times and stirred for 4-5 minutes, turning upside down during the stirring process to evenly disperse the copper powder;
[0017] Step 2: Ball milling dispersion:
[0018] After mechanical mixing, the iron, potassium chloride and copper mixed powders are loaded into a ball mill for ball milling dispersion, the ball-to-material ratio is 10:1, the rotation speed of the ball mill is 180-270 r / min, and during the ball milling dispersion process, the ball mill runs for 30-45 minutes and stops for 3-5 minutes to avoid excessive heat generation in the ball mill jar due to friction, and the ball milling time is 80-110 minutes;
[0019] Step 3: Electric spark sintering:
[0020] The iron, potassium chloride and copper mixed powder dispersed by ball milling is solidified by electric spark sintering process, the sintering temperature is 570-790 degrees, the sintering pressure is 0.5-1.3kN, and the holding time is 5-8 minutes;
[0021] Furthermore, in the iron-based bone implant with an acidified passivation film that accelerates dissolution, the rotation speed of the ball mill is 230 r / min.
[0022] Furthermore, in the iron-based bone implant with an acidified passivation film that accelerates dissolution, the electric spark sintering temperature is 620-730 degrees.
[0023] Furthermore, in the iron-based bone implant with an acidified passivation film that accelerates dissolution, the electric spark sintering pressure is 0.6-1.1 kN.
[0024] In the present invention, the electric spark sintering process used can quickly form the iron-potassium chloride-copper bone implant, and the fast heating rate and lower processing temperature significantly reduce the grain growth rate in the bone implant, which plays a fine grain strengthening effect. At the same time, during the melting and solidification process of the iron-potassium chloride-copper bone implant, the powder does not deform due to the very low pressure, which ensures the uniformity of the chemical composition, thereby improving the plasticity and resistance index of the bone implant and ensuring the mechanical stability of the bone implant during degradation.
[0025] After copper is added in the present invention, a part of the cuprous ions generated by the dissolution of the copper will form cuprous chloride, and then the cuprous chloride will hydrolyze to cause the acidity inside the passivation film, thereby further strengthening the acidic environment inside the passivation film caused by the hydrolysis of the cuprous ions. The internal acidic environment promotes the dissolution of the passivation film from the inside and inhibits the formation of the passivation film, ultimately making the passivation film loose and porous, reducing the shielding and blocking effect of the passivation film on the reaction medium.
[0026] The copper content needs to be strictly controlled in the present invention, although copper is a kind of essential trace element for human body, and has many biological functions and benefits for human body. However, when the copper ion concentration in cells exceeds the physiological needs of cells, copper ions will promote the formation of free radicals and oxidized proteins, causing the cell membrane potential to decrease, thereby leading to cell death. If the copper addition is limited, the effect of improving the corrosion rate of iron matrix is limited, and it is difficult to play the role of accelerating degradation, so it is necessary to reasonably select the powder ratio, and the copper particle size will also affect the corrosion effect.
[0027] The electric spark sintering process has a great influence on the forming performance of iron-potassium chloride-copper bone implants. If the electric spark sintering temperature is low, the mixed powder is difficult to melt completely, the molded part contains powder particles and is soft, and the mechanical integrity of the molded sample is poor; if the electric spark burning pressure is small, the density is greatly affected and the densification performance is low.
[0028] Compared with the prior art, the present invention has the following advantages:
[0029] (1) In the present invention, the iron-potassium chloride-copper bone implant can gradually degrade as the bone tissue is repaired, and the degradation process can be regulated by changing the copper content and the microstructure of the iron-potassium chloride-copper antibacterial bone implant to improve the degradation of the bone implant.
[0030] (2) In the present invention, the cuprous ions react with the chloride ions to generate cuprous chloride, which undergoes a hydrolysis reaction to induce an acidic environment, thereby promoting the dissolution of the passivation film and increasing the overall corrosion rate.
[0031] (3) In the present invention, the potassium chloride can maintain the excitability of nerve muscles and the normal function of the myocardium. At the same time, the released potassium ions are the main cations in the intracellular fluid, an important component for maintaining the intracellular osmotic pressure, and participate in many enzymatic reactions and physiological processes, thereby improving the biocompatibility of bone implants. DETAILED DESCRIPTION
[0032] Example 1
[0033] The average particle size of the copper powder is 47 microns. 0.9wt.% of the copper powder is weighed and dried at a constant temperature, and then introduced into iron powder with an average particle size of 61 microns and potassium chloride powder (3.7wt.%) with an average particle size of 27 microns in 4 equal amounts, and stirred for 5 minutes. During the stirring process, the mixture of the iron powder, copper powder and potassium chloride powder is turned upside down to evenly disperse the copper powder. After mechanical mixing, the mixture of the iron powder, copper powder and potassium chloride powder is loaded into a ball mill for ball milling dispersion, the ball-to-material ratio is 10:1, the speed of the ball mill is 230r / min, and during the ball milling dispersion process, the ball mill runs for 40 minutes and stops for 5 minutes, and the ball milling time is 97 minutes. After ball milling dispersion, the mixture of the iron powder, copper powder and potassium chloride powder is solidified and formed by an electric spark sintering process, the sintering temperature is 690 degrees, the sintering pressure is 0.9kN, and the insulation time is 6 minutes.
[0034] Implementation effect: After the iron-potassium chloride-copper bone implant prepared by the method was washed in distilled water, it corroded quickly and evenly in the immersion experiment, and the corrosion depth was 31 microns after 6 days.
[0035] Example 2
[0036] The average particle size of the copper powder is 47 microns. 1.4wt.% of the copper powder is weighed and dried at a constant temperature, and then introduced into iron powder with an average particle size of 61 microns and potassium chloride powder (3.7wt.%) with an average particle size of 27 microns in 4 equal amounts, and stirred for 5 minutes. During the stirring process, the mixture of the iron powder, copper powder and potassium chloride powder is turned upside down to evenly disperse the copper powder. After mechanical mixing, the mixture of the iron powder, copper powder and potassium chloride powder is loaded into a ball mill for ball milling dispersion, the ball-to-material ratio is 10:1, the speed of the ball mill is 260r / min, and during the ball milling dispersion process, the ball mill runs for 40 minutes and stops for 5 minutes, and the ball milling time is 107 minutes. After ball milling dispersion, the mixture of the iron powder, copper powder and potassium chloride powder is solidified and formed by an electric spark sintering process, the sintering temperature is 730 degrees, the sintering pressure is 1.1kN, and the insulation time is 6 minutes.
[0037] Implementation effect: After the iron-potassium chloride-copper bone implant prepared by the method was washed in distilled water, it corroded faster and more evenly in the immersion experiment. After 6 days, the corrosion depth was 27 microns.
[0038] Example 3
[0039] The average particle size of the copper powder is 47 microns. After weighing 0.4wt.% of the copper powder and drying it at a constant temperature, it is introduced into iron powder with an average particle size of 61 microns and potassium chloride powder (3.7wt.%) with an average particle size of 27 microns in three equal amounts and stirred for 5 minutes. During the stirring process, the mixture of the iron powder, copper powder and potassium chloride powder is turned upside down to evenly disperse the copper powder; after mechanical mixing, the mixture of the iron powder, copper powder and potassium chloride powder is loaded into a ball mill for ball milling dispersion, the ball-to-material ratio is 10:1, the speed of the ball mill is 190r / min, and during the ball milling dispersion process, the ball mill runs for 40 minutes and stops for 5 minutes, and the ball milling time is 83 minutes; after ball milling dispersion, the mixture of the iron powder, copper powder and potassium chloride powder is solidified and formed by an electric spark sintering process, the sintering temperature is 630 degrees, the sintering pressure is 0.8kN, and the insulation time is 6 minutes;
[0040] Implementation effect: After the iron-potassium chloride-copper bone implant prepared by the method was washed in distilled water, it corroded evenly in the immersion experiment, and the corrosion depth was 19 microns after 6 days.
[0041] Example 4
[0042] The average particle size of the copper powder is 47 microns. After weighing 0.7wt.% of the copper powder and drying it at a constant temperature, it is introduced into iron powder with an average particle size of 61 microns and potassium chloride powder (3.7wt.%) with an average particle size of 27 microns in equal amounts three times and stirred for 5 minutes. During the stirring process, the mixture of the iron powder, copper powder and potassium chloride powder is turned upside down to evenly disperse the copper powder; after mechanical mixing, the mixture of the iron powder, copper powder and potassium chloride powder is loaded into a ball mill for ball milling dispersion, the ball-to-material ratio is 10:1, the speed of the ball mill is 210r / min, and during the ball milling dispersion process, the ball mill runs for 40 minutes and stops for 5 minutes, and the ball milling time is 93 minutes; after ball milling dispersion, the mixture of the iron powder, copper powder and potassium chloride powder is solidified and formed by an electric spark sintering process, the sintering temperature is 650 degrees, the sintering pressure is 0.9kN, and the insulation time is 6 minutes;
[0043] Implementation effect: After the iron-potassium chloride-copper bone implant prepared by the method was washed in distilled water, it corroded faster and more evenly in the immersion experiment, and the corrosion depth was 23 microns after 6 days.
[0044] Comparative Example 1
[0045] The other conditions were consistent with those in Example 1, except that copper powder, iron and potassium chloride (3.7 wt.%) mixed powder were stirred and mixed in a mass ratio of 17:83 to obtain an iron-based bone implant with an acidified passivation film that accelerates dissolution. Tests found that the biological toxicity increased significantly, which may be due to the copper ion concentration exceeding the physiological needs of the cells, leading to cell death.
[0046] Comparative Example 2
[0047] The other conditions were consistent with those in Example 1, except that copper powder, iron and potassium chloride (3.7 wt.%) mixed powder were stirred and mixed in a mass ratio of 0.2:99.8 to obtain an iron-based bone implant with an acidified passivation film that accelerates dissolution. After testing, it was found that the antibacterial performance was poor and the corrosion rate of the sample was slow, which was lower than that of the sample in Example 1.
[0048] Comparative Example 3
[0049] The other conditions were consistent with those in Example 2, except that the spark sintering temperature was 370 degrees, and an iron-based bone implant with an acidified passivation film that accelerated the dissolution was obtained. Tests found that a small amount of powder inside the sample was not consolidated, and the mechanical properties were significantly reduced.
[0050] Comparative Example 4
[0051] The other conditions were consistent with those in Example 1, except that the ball-to-material ratio was 4:1, the rotation speed of the ball mill was 60 r / min, and the ball milling time was 23 minutes. An iron-based bone implant with an acidified passivation film that accelerated the dissolution was obtained, and a surface morphology with obvious corrosion and unevenness was found.
[0052] It can be seen from Examples 1, 2, 3 and 4 and Comparative Examples 1, 2, 3 and 4 that the components and preparation process of the present invention are an organic whole, and when any one or several key parameters are not within the protection scope of the present invention, the effect is significantly reduced. By comparing the internal aspects of Example 1 and Example 2, Example 3 and Example 4 of the present invention, it is found that the preferred embodiment of the present invention has an unexpected effect.
Claims
1. An iron-based bone implant with an acidified passivation film that accelerates the dissolution, which is composed of 3.7wt.% of iron, potassium chloride, and copper, wherein the mass percentage of copper is 0.3-1.5wt.%.
2. The iron-based bone implant with acidified passivation film that accelerates dissolution according to claim 1, characterized in that: In the iron-based bone implant with acidified passivation film that accelerates dissolution, the mass percentage of copper is 0.5-1.2wt.%.
3. The iron-based bone implant with acidified passivation film that accelerates dissolution according to claim 1, characterized in that: In the iron-based bone implant with acidified passivation film that accelerates dissolution, the mass percentage of copper is 0.9wt.%.
4. The iron-based bone implant with acidified passivation film that accelerates dissolution according to claim 1, characterized in that: In the iron-based bone implant with acidified passivation film that accelerates dissolution, the copper powder has a size of 30-60 microns, the iron powder has a size of 50-70 microns, and the potassium chloride powder has a size of 10-45 microns.
5. The iron-based bone implant with acidified passivation film that accelerates dissolution according to claim 1, characterized in that: The porosity of the iron-based bone implant with an acidified passivation film that accelerates dissolution is 17-29%.
6. The iron-based bone implant with acidified passivation film that accelerates dissolution according to claim 5, characterized in that: The porosity of the iron-based bone implant with an acidified passivation film that accelerates dissolution is 23-27%.
7. A method for preparing an iron-based bone implant with an acidified passivation film that accelerates dissolution according to any one of claims 1 to 6, characterized in that: The steps include: Step 1 Mechanical Mixing: After the copper powder is dried at a constant temperature, a certain mass is weighed and added to a mixed powder of iron and potassium chloride with a mass percentage of 3.7 wt.% in 2-3 equal amounts in 2-3 times, and stirred for 4-5 minutes, turning the powder upside down during the stirring process to evenly disperse the copper powder; Step 2: Ball milling dispersion: After mechanical mixing, the iron, potassium chloride and copper mixed powders are loaded into a ball mill for ball milling dispersion, the ball-to-material ratio is 10:1, the rotation speed of the ball mill is 180-270 r / min, and during the ball milling dispersion process, the ball mill runs for 30-45 minutes and stops for 3-5 minutes to avoid excessive heat generation in the ball mill jar due to friction, and the ball milling time is 80-110 minutes; Step 3: Electric spark sintering: The iron, potassium chloride and copper mixed powder dispersed by ball milling is solidified and formed by electric spark sintering process, the sintering temperature is 570-790 degrees, the sintering pressure is 0.5-1.3 kN, and the insulation time is 5-8 minutes.
8. The method for preparing an iron-based bone implant with an acidified passivation film that accelerates dissolution according to claim 7, characterized in that: The rotation speed of the ball mill is 230 r / min.
9. The method for preparing an iron-based bone implant with an acidified passivation film that accelerates dissolution according to claim 7, characterized in that: The electric spark sintering temperature is 620-730 degrees.
10. The method for preparing an iron-based bone implant with an acidified passivation film that accelerates dissolution according to claim 7, characterized in that: The spark burning pressure is 0.6-1.1kN.
Citation Information
Patent Citations
Implantable medical devices comprising bio-degradable alloys with enhanced degradation rates
CN105358184A
Preparation method for corrosion-resisting high-tenacity metal ceramic
CN108179342A
3D printing PCL(Polycaprolactone)-Cu bone tissue engineering scaffold and preparation method thereof
CN108853582A
Zinc-cooper coating for bone implantation and preparation method thereof
CN109652771A
Implantable medical devices comprising bio-degradable alloys with enhanced degradation rates
CN110074880A
